1979
DOI: 10.1002/cber.19791120715
|View full text |Cite
|
Sign up to set email alerts
|

Eine umkehrbare Gerüstumlagerung im trans‐Erythrinan‐Ringsystem, I. Erste Beobachtung und Versuch einer Deutung

Abstract: „Diol A”︁ 1 der trans‐Erythrinan‐Reihe zeigt im Gegensatz zu „Diol B”︁ 3 der cis‐Reihe ein ungewöhnliches Verhalten. Durch Acetylierung entsteht unter Umlagerung des Ringsystems das Diacetat 17, dessen Verseifung wieder zum Ausgangsmaterial 1 zurückführt. Die Stereochemie der umkehrbaren Gerüstumlagerung zeigen die Formeln 1a und 17a. Die Ringerweiterung zu 17 erkennt man im 1 H‐NMR‐Spektrum an der charakteristischen Hochfeldverschiebung des Signals für das aromatische Proton an C‐14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Mondon and Nestler [174] have also described ring-closure reactions leading to the formation of the new cyclic ethers (158a), (158b) and (159) having the cw-erythrinan skeleton. Furthermore, Mondon et al [175] have reported that acetylation of the diol (160) yielded the rearranged product (161a) which reverted to 160 on hydrolysis. The corresponding eis-diol formed a monoacetate without any rearrangement.…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mondon and Nestler [174] have also described ring-closure reactions leading to the formation of the new cyclic ethers (158a), (158b) and (159) having the cw-erythrinan skeleton. Furthermore, Mondon et al [175] have reported that acetylation of the diol (160) yielded the rearranged product (161a) which reverted to 160 on hydrolysis. The corresponding eis-diol formed a monoacetate without any rearrangement.…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%
“…15,16-Dimethoxy-2,8-dioxo-l, 7-cycloerythrinan earlier prepared by a concerted intermolecular alkylation of the 17^-mesylate [43], has been synthesized from homoveratrylamine in 37 per cent yield [182]. The reaction of isoquinolinopyrrolinedione (174) with 1,3-di-O-substituted butadienes proceeded in a regiospecific and regioselective manner to give erythrinan derivatives (175) and (176) (Fig. The Diels-Alder reaction of Δ -pyrroline-4,5-diones with activated butadienes which proceeds in a regio-and stereo-selective manner [183] has been applied to the synthesis of ring-D-functionalized erythrinan derivatives in acceptable yields [184][185].…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%